Optimalisasi Penggunaan Mendeley dalam Penulisan Karya Ilmiah Mahasiswa - A. Reski Almaida Dg Macenning; Anang Setiawan; Rostina Rostina; Satria Putra Jaya Negara; Hasisa Haruna (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Scientific writing is an essential competency that must be mastered by university students, particularly in managing citations and references in accordance with academic standards. However, many students still face difficulties in producing consistent and accurate citations due to limited understanding and lack of utilization of supporting technologies. This community service activity aims to improve the knowledge and skills of Management students at Universitas Negeri Makassar (Class of 2023) in using Mendeley as a reference management tool. The training was conducted online via Zoom using lecture, demonstration, and hands-on training methods. The results indicate a significant improvement in students’ understanding of citation concepts and reference management, as well as their practical ability to use Mendeley for automatic citation and bibliography generation. Furthermore, the interactive online training approach proved to be effective in enhancing participant engagement and learning outcomes. This activity contributes to improving students’ academic literacy and supports the development of higher-quality scientific writing in accordance with academic standards.